CURRENT SOCIO-PEDAGOGICAL CHALLENGES IN IMPLEMENTING AND DEVELOPING GENERATIVE ARTIFICIAL INTELLIGENCE TECHNOLOGIES IN THE PROCESS OF TEACHING ENGLISH IN HIGHER EDUCATION - Nigmatova Nozimaxon (International Scientific and Current Research Conferences, 2025)
This article analyzes the current socio-pedagogical challenges associated with implementing and developing generative artificial intelligence technologies in the process of teaching English in higher education institutions. The study provides a research-based discussion of the impact of AI technologies on the educational process, including pedagogical, social, and ethical issues, as well as methodological constraints in their application. In addition, the necessary conditions and promising directions for the effective implementation of these technologies are identified.